2021
DOI: 10.3390/e23101321
|View full text |Cite
|
Sign up to set email alerts
|

Alien Attack: A Non-Pharmaceutical Complement for ADHD Treatment

Abstract: Mental health issues are among the most common health issues nowadays, with attention-deficit hyperactivity disorder (ADHD) being the most common neurobehavioral disorder affecting children and adolescents. ADHD is a heterogeneous disease affecting patients in various cognitive domains that play a key role in daily life, academic development, and social abilities. Furthermore, ADHD affects not only patients but also their families and their whole environment. Although the main treatment is based on pharmacothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…For example, prior work shows that adding game features and machine learning-the use of participant data in real-time and algorithms to gradually adjust difficulty level to challenge participants appropriately-to the CPT have been especially beneficial for the engagement of individuals with EF impairments such as those with ADHD [36,37]. Similarly, Ahufinger and Herrero-Martín [38] found that participants with ADHD ages 6-13 completed GAs of EF under the time allocated, with feedback from participants that they would have preferred increased task difficulty. Additionally, GAs of EF assessments can also be highly useful for research with neurotypical samples: typically developing participants without psychiatric disorders often show performance in the relatively narrow ranges in traditional EF assessments [39], and GAs permit a more nuanced measurement of performance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, prior work shows that adding game features and machine learning-the use of participant data in real-time and algorithms to gradually adjust difficulty level to challenge participants appropriately-to the CPT have been especially beneficial for the engagement of individuals with EF impairments such as those with ADHD [36,37]. Similarly, Ahufinger and Herrero-Martín [38] found that participants with ADHD ages 6-13 completed GAs of EF under the time allocated, with feedback from participants that they would have preferred increased task difficulty. Additionally, GAs of EF assessments can also be highly useful for research with neurotypical samples: typically developing participants without psychiatric disorders often show performance in the relatively narrow ranges in traditional EF assessments [39], and GAs permit a more nuanced measurement of performance.…”
Section: Introductionmentioning
confidence: 99%